A study of associated congenital anomalies with biliary atresia - Lucky Gupta; Veereshwar Bhatnagar (Wolters Kluwer Medknow Publications, 2016)
Background/Purpose: This study aims to analyze the incidence and type of various associated anomalies among infants with extrahepatic biliary atresia (EHBA), compare their frequency with those quoted in the existing literature and assess their role in the overall management. Materials and Methods: A retrospective study was performed on 137 infants who underwent the Kasai procedure for EHBA during the past 12 years. The medical records were reviewed for the incidence and type of associated anomalies in addition to the details of the management of the EHBA. Results: Of the137 infants, 40 (29.2%) were diagnosed as having 58 anomalies. The majority of patients had presented in the 3 rd month of life; mean age was 81 ± 33 days (range = 20-150 days). There were 32 males and 8 females; boys with EHBA had a higher incidence of associated anomalies. Of these 40 patients, 22 (37.9%) had vascular anomalies, 13 patients (22.4%) had hernias (umbilical-10, inguinal-3), 7 patients (12.1%) had intestinal malrotation, 4 patients (6.8%) had choledochal cyst, 1 patient (1.7%) had Meckel's diverticulum, 3 patients (5%) had undergone prior treatment for jejunoileal atresias (jejunal-2, ileal-1), 2 patients (3.4%) had undergone prior treatment for esophageal atresia and tracheoesophageal fistula, 2 patients (3.4%) had spleniculi, and 2 patients (3.4%) were diagnosed as having situs inversus. Conclusions: The most common associated anomalies in our study were related to the vascular variation at the porta hepatis and the digestive system. The existence of anomalies in distantly developing anatomic regions in patients with EHBA supports the possibility of a "generalized" insult during embryogenesis rather than a "localized" defect. In addition, male infants were observed to have significantly more associated anomalies as compared with the female infants in contrast to earlier reports.